Impact on the Development of Labor Competences in the Municipality of San Vicente Del Caguan Caqueta-Colombia (Global Journal of Human-Social Science, 2022)
Training and developing general labor competencies CLG in people is one of the great challenges that secondary educational institutions in Colombia must assume in order to contribute to the productive and social world according to the needs and particularities of each territory which requires a curricular structuring that relates the objectives proposed from the framework of education with territorial approaches in the search to contribute to the development of the local economy cultural socio-political perspectives in marked post-conflict scenarios and the comprehensive training of subjects who are prepared to respond to the changing demands of the present and future in diverse environments In this sense this article presents the results of data analysis under multivariate statistical analysis with R software supported in a systemic framework from the Vester matrix to understand the training processes focused on the development of CLG in the Municipality of San Vicente of Cagu n Caquet
Keywords: general job skills; methodology; secondary education; curriculum; training programs and territorial approach